1996
DOI: 10.1111/j.1745-4565.1996.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION OF BDELLOVIBRIOS THAT PREY ON ESCHERICHIA COLI O157:H7 AND SALMONELLA SPECIES AND APPLICATION FOR REMOVAL OF PREY FROM STAINLESS STEEL SURFACES1

Abstract: Predatory bacteria of the genus Bdellovibrio that prey upon Escherichia coli O157:H7 and Salmonella species were isolated from soil and sewage samples. Bdellovibrio isolates 45k (from soil) and 88e (from sewage) attacked and lysed the E. coli and Salmonella strains tested, with log10 reductions ranging from 2.5 to 7.9 CFU/mL after 7h incubation, using a two‐membered culture system. The predators showed activity against the bacteria within the temperature range of 19 to 37C. Bdellovibrio isolate 45k reduced a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 27 publications
3
46
2
Order By: Relevance
“…Shilo (1966) and Lambina et al (1987) confirmed that these bacteria play a role in controlling the population size of bacteria in biofilms. In this context, Fratamico and Cooke (1996) showed that these bacteria reduced the number of E. coli by two logs, which suggests that these predatory bacteria could usefully serve as agents for the control of pathogens. Moreover, Markelova (2010) confirmed that Bdellovibrio caused lysis of Alcaligenes sp., Campylobacter sp., Erwinia sp., Escherichia sp., Helicobacter sp., Pseudomonas sp., Legionella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Shilo (1966) and Lambina et al (1987) confirmed that these bacteria play a role in controlling the population size of bacteria in biofilms. In this context, Fratamico and Cooke (1996) showed that these bacteria reduced the number of E. coli by two logs, which suggests that these predatory bacteria could usefully serve as agents for the control of pathogens. Moreover, Markelova (2010) confirmed that Bdellovibrio caused lysis of Alcaligenes sp., Campylobacter sp., Erwinia sp., Escherichia sp., Helicobacter sp., Pseudomonas sp., Legionella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Starting about a decade later, researchers began to think about the possible application of this unique bacteria in different applications, such as in fighting plant pathogens (10) and in reducing bacterial numbers/contamination in food industries (11). However, researchers were limited in their potential applications since genetic tools and knowledge were both limited, particularly for this bacterium.…”
Section: Historical Perspective the Early Years (1962-1992)mentioning
confidence: 99%
“…However, the incubation period required was extended compared to tests performed at higher temperatures (30 and 37 o C). In another study by the same group, the authors wanted to test the ability of B. bacteriovorus to remove the gram negative bacteria from the surfaces of food processing equipment (11). Their isolated strains of B. bacteriovorus were capable of lysing E. coli O157:H7 and Salmonella sp.…”
Section: Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Does fragmentation increase the persistence of the prey population? Furthermore, given that B. bacteriovorus has shown potential to protect crops and reduce biofouling [26][27][28][29], it would be useful to know how its effectiveness in structured habitats relates to its effectiveness as measured in well-mixed (unstructured) culture flasks [30][31][32]. In this regard, B. bacteriovorus has also attracted significant interest because of its potential to eradicate bacterial biofilms which are spatially structured at the microscale [33,34].…”
Section: Introductionmentioning
confidence: 99%